Baryogenesis from ultralight primordial black holes and strong gravitational waves from cosmic strings. Issue 8 (11th August 2021) - Datta, Satyabrata; Ghosal, Ambar; Samanta, Rome
Abstract: Ultralight primordial black holes (PBHs)(≲10 9 g) completely evaporate via Hawking radiation (HR) and produce all the particles in a given theory regardless of their other interactions. If the right handed (RH) neutrinos are produced from PBH evaporation, successful baryogenesis via leptogenesis predicts mass scale of RH neutrinos as well as black holes. We show that, given the lepton number violation (generation of RH neutrino masses) in the theory is a consequence of a gauged U(1) breaking which is then followed by the formation of PBHs, a network of cosmic strings naturally gives rise to strong stochastic gravitational wave (GW) signal at the sensitivity level of pulsar timing arrays (PTA) and LIGO5. Besides, due to a transient period of black hole domination in the early universe, for which baryon asymmetry is independent of initial PBH density, a break in the GW spectra occurs around MHz frequency. Therefore, to observe the break along with the usual GW signal by the emission of gravitons via HR, GW detectors at higher frequencies are called for. The recent finding by the NANOGrav PTA of a stochastic common spectrum process (interpreted as GWs) across many pulsars is in tension with PBH baryogenesis for large cosmic string loops (α ≃ 0.1).